General, specific combining ability, and heritability in potato genotypes (Solanum tuberosum L.) for agronomic traits - Marmolejo-Gutarra, Doris; Arias, Jhosellin; Marín, Mónica (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Potato (Solanum tuberosum L.) is a key crop in Peru due to its nutritional value and its potential for agronomic genetic improvement, which justifies further research in the selection of promising parents and crosses. This study aimed to estimate general combining ability (GCA), specific combining ability (SCA), and heritability for key agronomic traits: plant height, earliness, and the number and weight of tubers per plant, under the climatic conditions of Huancayo, Peru. Sixteen F₁ families derived from a full diallel cross (Griffing's model I, method I, fixed effects) among four parents (Mariva, Redondo, Redondo Achatado, and Oblongo) were evaluated. The trial was conducted using a randomized complete block design with three replications. The analysis included ANOVA, estimates of GCA, SCA, and reciprocal effects. Highly significant differences (p < 0.01) were detected among the combinations. Mariva showed the highest GCA for plant height (5.266), while the Redondo Achatado × Redondo cross exhibited the highest SCA (6.404); for earliness, the GCA of Redondo Achatado (0.056) and the SCA of Redondo Achatado × Mariva (0.952) were outstanding; regarding tuber number per plant, Redondo had the highest GCA (3.258) and the Redondo × Redondo Achatado cross the highest SCA (8.982); for tuber weight, Redondo had the best GCA (0.107) and Oblongo × Redondo the highest SCA (0.449). Heritability ranged from 0.419 to 0.596, indicating moderate to high genetic variation. The high values of GCA and SCA, along with the observed heritability, confirm the potential of these parents to improve potato yield.